Fluid-dependent shear-wave splitting in a poroelastic medium with conjugate fracture sets - Galvin, R.; Gurevich, Boris; Sayers, C. (EAGE Publications BV, 2004)
Dependency of shear-wave splitting in fractured reservoirs on the properties of the filling fluid may provide a useful attribute for identifying reservoir fluids. If the direction of wave propagation is not perpendicular or parallel to the plane of fracturing, the wave polarized in the plane perpendicular to the fractures is a quasi-shear mode, and therefore the shear-wave splitting will be sensitive to the fluid bulk modulus. The magnitude of this sensitivity depends upon the extent to which fluid pressure can equilibrate between pores and fractures during the period of the deformation. In this paper we use the anisotropic Gassmann equations and existing formulations for the excess compliance due to fracturing to estimate the splitting of vertically propagating shear-waves as a function of the fluid modulus for a porous medium with a single set of dipping fractures and with two conjugate fracture sets dipping with opposite dips to the vertical. This is achieved using two alternative approaches. In the first approach it is assumed that the deformation taking place is quasi-static. That is, the frequency of the elastic disturbance is low enough to allow enough time for fluid to flow between both the fractures and the pore space throughout the medium. In the second approach we assume that the frequency is low enough to allow fluid flow between a fracture set and the surrounding pore space, but high enough so that there is not enough time during the period of the elastic disturbance for fluid flow between different fracture sets to occur. It is found that the second approach yields a much stronger dependency of shear-wave splitting on the fluid modulus than the first one. This is a consequence of the fact that at higher wave frequencies there is not enough time for fluid pressure to equilibrate and therefore the elastic properties of the fluid have a greater effect on the magnitude of the shear-wave splitting.